2010
DOI: 10.1021/jp100851y
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of the B−BN System at 5 GPa

Abstract: The chemical interaction and phase relations in the B-BN system have been in situ studied at 5 GPa and temperatures up to 2800 K using X-ray diffraction with synchrotron radiation. The thermodynamic analysis of the B-BN system based on experimental data allowed us to construct equilibrium and metastable phase diagrams of the system at 5 GPa. The only thermodynamically stable boron subnitride, B(13)N(2), melts incongruently at 2600 K and forms eutectic equilibrium with boron at 2300 K and 4 at. % of nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Considerably less research has been carried out on the synthesis and properties of nonstoichiometric B 1-x N x boron nitrides. Mainly, boron subnitrides (x<0.5) resembling the α-rhombohedral (rh) boron structure have attracted some interest in the last decades [12][13][14][15][16][17][18][19][20][21], inspired by the technological interest of boron-rich hard refractory compounds (B 4 C, B 6 O,…) [22].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Considerably less research has been carried out on the synthesis and properties of nonstoichiometric B 1-x N x boron nitrides. Mainly, boron subnitrides (x<0.5) resembling the α-rhombohedral (rh) boron structure have attracted some interest in the last decades [12][13][14][15][16][17][18][19][20][21], inspired by the technological interest of boron-rich hard refractory compounds (B 4 C, B 6 O,…) [22].…”
mentioning
confidence: 99%
“…Using this technique in combination with synchrotron x-ray diffraction, Solozhenko et al determined the structure of a new α-rh B 13 N 2 phase with N-B-N linear chains between B 12 icosahedra [12,15,17,18,23,24]. They also studied the phase diagram of the B-BN system and observed the formation of an I-tetragonal B 50 N 2-x B x solid solution [15,17]. Hubert and co-workers reported the HP-HT synthesis of an α-rh B 12 N 2 phase similar to B 6 O [16,25], but the results were questioned later on by the group of Solozhenko [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the other icosahedral boron-rich solids, in particular boron carbide, having been frequently addressed in the literature [1,6,17,20,25,27,28,30,35,36,84,91,[94][95][96][108][109][110][111][112][113][114], relatively few studies have so far been made on boron subnitride [19,[115][116][117][118][119][120]. For this reason, several issues about boron subnitride, for example its stable compositions, properties, as well as the correct representation of its basic structural unit, are still inconclusive.…”
Section: Boron Subnitridementioning
confidence: 99%
“…Due to the small variation of lattice parameters of the as-synthesized boron subnitrides found in experiments, it has been suggested that boron subnitride, instead of a solid solution, is an individual line compound [119]. Furthermore, due to the incompleteness of the reactions, the as-synthesized boron subnitrides had often poor crystalline quality, and were always found in a mixture with β-rhombohedral boron, hexagonal boron nitride and α-tetragonal boron subnitride, limiting accessibility to the properties of boron subnitride in experiments [119,120].…”
Section: Boron Subnitridementioning
confidence: 99%